Identifying and analyzing the factors affecting the outcomes of student selection in Farhangian University - Azimeh Motekalem (Institute of Management fekrenoandish, 2021)
Extended Abstract Abstract The aim of this study is to identify and analyze the factors affecting the outcomes of student selection in Farhangian University, which has been done in a mixed method. Delphi technique has been used in the qualitative part in this research. The statistical population of the study includes 550 professors of Farhangian University in the campuses located in three provinces of West and East Azarbayjan, and Ardabil. 27 persons were available through purposeful sampling in the qualitative stage, and 227 persons were chosen through cluster sampling in the quantitative stage. The research tool was a semi-structured interview in the qualitative part, which was validated by means of the participant's feedback method. In the quantitative part, a researcher-made questionnaire was used. Average values of extracted variances (AVE) in all components are higher than 0.7. Therefore, the reliability of the research questionnaire is confirmed. Coding method was used for qualitative data analysis, and structural equation modeling was used for quantitative data analysis using PLS version 3 software. Based on the findings of the qualitative department, the most important factors affecting the consequences of student selection in Farhangian University are: process-based selection, selection criteria, and selection tools. The results of the quantitative section show that the studied structural model is of good quality and the observed values are well reconstructed and the studied model has a high predictive ability which can predict the endogenous latent variable. Introduction Education is the foundation of social, economic, political and cultural development of any society and has the greatest impact on the promotion of society in various dimensions. Any fundamental change in society requires the transformation of the educational system of that society and the main axis of development of any educational system is the quality of teacher performance (Nazarpour, 2017). Formal education has been an inclusive system since the beginning of this century, first in advanced societies and then in all developing societies, and today there is no society in which this system has no role in its evolution and development (Golshan, 2018). But what is most important among the various teacher education programs is the issue of attracting and selecting the right people. This issue has always been important in the educational systems of most developed countries and has been prioritized in their educational programs (Soleymani & Motakallem & Namvar, 2021). In Finland, for example, the selection of qualified people for the teaching profession is a complex process, and the selection of these people takes place with ultimate precise. (Garbe & Shiel & Sulkunen, 2017). However, despite the importance of this issue, there are always disagreements about the process of selecting the right people, and these different perspectives should be benefitted to form a suitable program to select the right people (Kitchen & Petrarca, 2016). Undoubtedly, universities and teacher training centers are places that must use appropriate and sufficient criteria to select the right people from among the various candidates. If they refuse to play their role, the quality of selected individuals and even future teachers can not be guaranteed (Raths & Lyman, 2009). In any country, providing the favorable condition to achieve the positive and applicable results in the process of students' learning involves special attention to the process of selecting and training candidates to enter the profession of teaching in teacher training centers. Groundwater-Smit Mockler, 2009). Given the above, the process of selecting the right people to enter teacher training centers is of particular importance in the education system, and it seems that this issue has been neglected in the studies of researchers in the country. Therefore, the present study focuses on this main issue and seeks to answer the following questions: What are the factors affecting the consequences of student selection in Farhangian University? What are the most important factors in choosing the right student in Farhangian University? To what extent do these factors affect the outcome of student selection at Farhangian University? Theoretical framework Selecting the right people for the teaching profession is a step to accept or reject the applications of applicants for the teaching profession so that the most suitable and appropriate ones are selected. (Mirsepasi, 2015) The conditions for selecting the right people are the criteria and indicators individuals volunteering for the teaching profession must meet. In Unesco's manifest (UNESCO, 2017) concerning the "teacher training", the teacher is introduced as the axis and center of learning, and having effective and skillful teachers is considered the right of every child in the world, which is conditioned on the careful selection of interested and capable people to enter the profession. In this manifest, the selection of the appropriate teachers for the learners is introduced as one of the main factors in growth and development of the educational systems (Soleymani & Motakallem & Namvar, 2021). Mahdavi Hazaveh et al. (2017) in a study entitled "Good life, a perspective for children" while highlighting the importance and position of teachers in society, showed Given the position of this job in society, a teacher requires special qualifications, and certainly those involved in this field must be careful in choosing the right people to enter this sacred profession. Ragnarsdóttir & Jóhannesson (Ragnarsdóttir & Jóhannesson, 2014) in their study entitled, have investigated the admission process in Iceland. According to this research, due to the limited admission capacity to select the right people, each institution and center has defined some approximate criteria for itself, but what is common among all teacher training centers in this country includes criteria such as work experience, participate in social organizations and activities in them, having and cooperating in related and additional training (Nazarpour, 2017). Methodology The present study uses a mixed and exploratory design in which qualitative and quantitative data are collected and analyzed. In this research, Delphi technique has been used in the qualitative part. The present study began with the collection and analysis of qualitative data in which the most important factors affecting the consequences of student selection in Farhangian University were identified through interviews and three stages including open, axial and selective coding from the perspective of participants. In the second step, quantitative data were collected and analyzed. The statistical population of the study is 550 professors and lecturers of Farhangian University in the campuses of three provinces of West, East and Ardabil in 1399, of which 27 persons were available through purposeful sampling in the qualitative stage, and 227 persons in the quantitative stage by Cluster sampling were selected. The data collection tool was semi-structured in the qualitative stage of the interview. In order to collect quantitative data, a researcher-made questionnaire from the qualitative section of 35 questions was used. Structural equation model with PLS software was used to analyze the quantitative data. Discussion and Results Based on the findings of the qualitative department, the most important factors affecting the consequences of student selection in Farhangian University are: process-based selection, selection criteria, and selection tools. The results of the quantitative section show that the studied structural model is of good quality and the observed values are well reconstructed and the studied model has a high predictive ability and can predict the endogenous latent variable. Process-based selection elements, selection criteria, and selection tools can explain 43.3% of the variance of outcomes, which is significant. Also, the value for the outcome variable is equal to 0.508, which is considered strong. Therefore, it can be said that the studied structural model is of good quality and the observed values are well reconstructed and the studied model has a high predictive ability and can predict the endogenous latent variable.